Pengaruh Pendidikan Kesehatan Terhadap Peningkatan Pengetahuan Dan Sikap Penderita Diabetes Mellitus Dalam Pencegahan Luka Kaki Diabetik Di Puskesmas Jagir Kecamatan Wonokromo - Nurul Ramadhani Yaner (NERSMID : Jurnal Keperawatan dan Kebidanan, 2019)
Diabetes mellitus (DM) is a degenerative disease as a result of a metabolic disorder caused by the inability of the pancreas to produce insulin. The purpose of the study was to determine the effect of health education on improvement of knowledge and attitude of people with diabetes in the prevention of diabetic foot wounds in Puskesmas Jagir Wonokromo Surabaya. This study is included in the category of quantitative research with Quasy Experimental design and use pretest-posttest study design Control Group Design. The population in this study is 60 respondents were divided into two groups, 30 respondents into experimental group and a control group of 30 responders become. Data analysis techniques used by paired sample t-test and independent t-test simple.The results showed: There are differences in the level of knowledge after health education in experimental (X1 = 13.16)and control groups (X2 = 11.79) and no difference in attitude after education in the experimental (X1 = 56.09 ) and control groups (X2 = 53.19), there is the influence of education kesehatann to increased knowledge of diabetes mellitus in the prevention of diabetic foot wounds in Puskesmas Jagir Wonokromo Surabaya (p-value = 0.025 < 0,05), no effect of education on attitudes kesehatann diabetes mellitus in the prevention of diabetic foot wounds in Puskesmas Jagir Wonokromo Surabaya (p-value = 0.033 < 0,05).